2015
DOI: 10.1515/amm-2015-0484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling Time on Microstructure and Properties of AA6061/MWCNTS Composite Powders / Wpływ Czasu Mielenia Na Strukturę I Własności Proszk Ów Kompozytowyc H AA6061/MWCNTS

Abstract: The main purpose of this work is to determine the effect of milling time on microstructure as well as technological properties of aluminium matrix nanocomposites reinforced with multi-walled carbon nanotubes (MWCNTs) using powder metallurgy techniques, including mechanical alloying. The main problem of the study is the agglomeration and uneven distribution of carbon nanotubes in the matrix material and interface reactivity also. In order to reach uniform dispersion of carbon nanotubes in aluminium alloy matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Powder metallurgy has used a range of aluminium powders and CNT volume fractions to significant effect. For pre-and post-HIP, the tribological, density, stiffness, and compressive strength performance of the aluminium matrix nanocomposite were studied [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Powder metallurgy has used a range of aluminium powders and CNT volume fractions to significant effect. For pre-and post-HIP, the tribological, density, stiffness, and compressive strength performance of the aluminium matrix nanocomposite were studied [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…From previous literature, it is reported that the mechanical alloying process parameters could influence the mechanical properties of Al and its composites. Earlier researchers had experimented the effects of milling parameters on powders and suggested the most influencing factors are milling time, Ball To Powder Ratio (BTPR) and milling speed [8,9]. Fogagnolo et al [10] studied the effects of mechanical alloying process on microstructure and mechanical properties of the Al and its composites.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of European legal requirements, domestic resources of brown and hard coal, depreciation of most of operating power units in Poland, as well as energy security, trends in research and development of energy aim to build a modern power units with ultra-cool supercritical parameters, e.g. a temperature of 650-740 °C and pressure 30-35 MPa [1][2][3][4][5][6].…”
mentioning
confidence: 99%